Implicity and Redundancy: Two Poles of Linguistic Expression - ABRAHAMYAN, ASHOT (Bulletin of Yerevan University B: Philology, 2021)
In the studies on semantics, implicit meanings are commonly opposed to explicit ones, which, however, is only half right. Redundancy, as an overexpression, should be considered opposite to implicity, which, actually, is an underexpression, while pure explicity is the midway point in this opposition. Implicity and redundancy can be considered in different levels of language structure, and the higher the level, the greater the number and diversity of implicity and redundancy manifestations are. Implicity and redundancy are not absolute but only relative assessments of semantic features: these are two poles of linguistic expression, with any linguistic expression, any communicative act occupying a midway position between them.